(3GdQSGdI GdNJGfjI aj GdCMGOjK GdfHhjIs - (3GdbSWfWjfj, EHQGgje Hf CMeO Hf EHQGgjes
(3ChdgG (B:s
(3HSeg (B( (3cPG (B) (3JbOS hHg CSJYjf GdMeO ddg GdPj LYd Cgd GdMOjK aj GdMOjK hGdbOje hHYO ajbhd EHQGgje Hf GMeO deG QCjJ Cf CLeY CMGOjK hGQOI aj Mb GdNJGf hZjQg ef GdaWQI ef cJH eYJHQI cGdHNGQj heSde hEHf eGLI hSff CHj OGhO hGdJQePj hGdfSGFj hZjQ Pdc hSejJg GdNJGfjI aj CMGOjK fHhjI (B( (3cPG (B)s
(3BNQgG (B:s
(3hQhj Cf QLdG ONd aj eSLO QShd Gddg Udi Gddg Ydjg hSde hTGQHg Whjd aRLQg Yf Pdc aPgH GdQLd abU fUa TGQHg Ke ONd GdeSLO abGd dg GdfHj Udi Gddg Ydjg hSde hLOJ fUa GdEjeGf haj HYV GdQhGjGJ ef bU TGQHg jYWi Hcd YTQI MSfIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3TgGOGJ GdQhGjI (B: s
(3GdELGRGJ h GdSeGYGJ (B:s
Keywords: (3GdMOjK hGdeUWdMs